Sewing needle: a rare cause of intra-cardiac foreign body in a 3-year-old child. (20th June 2016) - Choudhary, Sandeep; Pujar Venkateshacharya, Suresh; Reddy, Chinnaswamy
Abstract: Sewing needles are rare causes of penetrating cardiac injury. Suicidal attempt, accidental penetration, domestic violence, and child abuse are likely causes for such injury. 1 Owing to their sharp nature, needles can rapidly migrate through the tissues. Fatalities are due to cardiac tamponade, infection, peripheral embolism, and valve dysfunction.